2003
DOI: 10.1109/tip.2003.810591
|View full text |Cite
|
Sign up to set email alerts
|

Improved MPEG-4 still texture image coding under noisy environment

Abstract: This paper describes the performance of the MPEG-4 still texture image codec in coding noisy images. As will be shown, when using the MPEG-4 still texture image codec to compress a noisy image, increasing the compression rate does not necessarily imply reducing the peak-signal-to-noise ratio (PSNR) of the decoded image. An optimal operating point having the highest PSNR can be obtained within the low bit rate region. Nevertheless, the visual quality of the decoded noisy image at this optimal operating point is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…Instead, at middle and high bit rates, increasing bit rate will give rise to lower PSNR. Similar behavior of noisy video/image coding has also been reported in [22], [26], [27]. Here, we give a heuristic explanation: with high bit rate, the quantization step size is very small, and all the information of the input video including the noise can be preserved.…”
Section: B Performance Of the Proposed Encoding Scheme Veidsupporting
confidence: 67%
“…Instead, at middle and high bit rates, increasing bit rate will give rise to lower PSNR. Similar behavior of noisy video/image coding has also been reported in [22], [26], [27]. Here, we give a heuristic explanation: with high bit rate, the quantization step size is very small, and all the information of the input video including the noise can be preserved.…”
Section: B Performance Of the Proposed Encoding Scheme Veidsupporting
confidence: 67%
“…The first approach (A1) is to compress original data directly, i.e. without using the homomorphic transform 23 In general, the behaviour of dependencies nf PSNR and or PSNR on bpp in this case is similar 13 (see Fig. 3,a) to the behaviour of the corresponding curves in Fig.…”
Section: Approaches To Automatic Lossy Compression Of Noisy Imagesmentioning
confidence: 88%
“…And, according to such a criterion (commonly, PSNR that will be further denoted as PSNR nf ), there exists such CR for which PSNR nf is maximal. This CR is called optimal operation point (OOP) 10,23 . Third, an image to be compressed can be a subject to prefiltering 10,14 and a decompressed image can be post-processed 10,15,23 .…”
Section: Introductionmentioning
confidence: 99%
“…That is why, lossy compression methods are much more often used for noisy image coding in such applications as remote sensing [2,3], environment monitoring systems [4,5], ultrasound and X-ray medical imaging [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Lossy compression of noisy images possesses one very important advantage: it performs noise reduction simultaneously with image compression, i.e. decreasing a compressed image size with respect to an original image [2][3][4][5][6][7][8]. This positive phenomenon is emphasized by many authors and it is observed for different noise types.…”
Section: Introductionmentioning
confidence: 99%